Primaquine-chitosan Nanoparticle Improves Drug Delivery to Liver Tissue in Rats - Louisa, Melva; Hawa, Putrya; Purwantyastuti, Purwantyastuti; Mardliyati, Etik; Freisleben, Hans-Joachim (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Primaquine is one of the essential medicines used to treat malaria due to Plasmodium vivax. Primaquine acts by eradicating hypnozoites in the liver, and its effect is dependent on the drug concentrations in the target tissue. The present study aimed to prepare primaquine in nanoparticle formulation using chitosan as carriers and improve on-target primaquine delivery to the liver. Methods: Primaquine-loaded chitosan nanoparticles were prepared using the ionic gelation method variations. Then, the resulting primaquine-chitosan nanoparticles were administered to the rats and compared with conventional primaquine. Afterward, plasma and liver concentrations of primaquine were quantified. Results: The primaquine-chitosan nanoparticles obtained were at 47.9 nm. The area under the curve for primaquine-chitosan nanoparticles resulted lower in the area under the curve (AUC) and Cmax, 0.46 and 0.42 times of conventional primaquine, respectively. However, no differences were found in time to reach Cmax (Tmax). Primaquine liver concentrations obtained with primaquine-chitosan nanoprimaquine resulted in 3 times higher than primaquine concentration. Conclusion: Enhanced drug delivery to rat liver tissue by primaquine-chitosan nanoparticles may improve on-target drug delivery to the liver, enhance primaquine ant hypnozoites effects, and reduce unwanted side effects in the circulation.